(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the profile of interactions between flavonoids against key proteins of SARS-CoV-2 infection, and secondarily, to analyze the properties of these chemical constituents against Lipinski’s Rule as potential drug candidates. Methodology: This study is characterized as a quantitative descriptive experimental type, through computational methods, where AutoDock Tools, AutoDock Vina, Biovia Discovery Studio and ChimeraX were used to perform the molecular coupling between the main flavonoids present in plants from the Lavandula genus with the M protein and the complex between the Angiotensin-2 Converting Enzyme and the S protein receptor binding domain of SARS-CoV-2. Results: Analyzing the isolated interactions of each flavonoid with the proteins, it is noted that the compounds showed more favorable interactions with the Angiotensin 2 Converting Enzyme and the receptor binding domain. For Lipinski’s rule, Delphinidin presented two violations, being considered, in this context, an unpromising molecule. Conclusion: It is concluded, therefore, that flavonoids in silico present an inhibitory potential for the tested proteins, being more favorable to the Angiotensin 2 Converting Enzyme complex with the receptor binding domain. In view of Lipinski’s rule, only Delphinidin showed low potential as a drug candidate, however, the use of nanocarriers could circumvent some of its limitations.